A Longitudinal Study of Demographic Factors Associated With Stressors and Symptoms in African Refugees. (28th October 2013) - Perera, Sulani; Gavian, Margaret; Frazier, Patricia; Johnson, David; Spring, Marline; Westermeyer, Joseph; Butcher, James; Halcon, Linda; Robertson, Cheryl; Savik, Kay; Jaranson, James
Abstract : The objectives of this study were to assess differences in premigration, transit, and resettlement stressor exposure and post traumatic stress disorder (PTSD) symptoms as a function of demographic characteristics (i.e., gender, ethnicity, age, time in United States) and to examine the concurrent and longitudinal relations between stressor exposure and PTSD symptoms. The sample consisted of adult (18–78 years) Somali and Oromo refugee men and women ( N = 437). Qualitative data regarding participants' self‐nominated worst stressors collected at Time 2 (T2) informed the development of quantitative scales assessing premigration, transit, and resettlement stress created using items collected at Time 1 (T1). PTSD symptoms were measured at both T1 and T2. Quantitative analyses showed that levels of stressor exposure and PTSD symptoms differed as a function of refugee demographic characteristics. For example, Oromo, more recent, women, and older refugees reported more premigration and resettlement stressors. Oromo refugees and refugee men reported more PTSD symptoms in regression analyses with other factors controlled. Premigration, transit, and resettlement stressor exposure generally was associated with higher PTSD symptom levels. Results underscore the importance of assessing stress exposure comprehensively throughout the refugee experience and caution against overgeneralizing between and within refugee groups.